Effect of ageing and priming on vigour parameters of wheat (Triticum aestivum) - CHAUHAN, D S; DESWAL, D P (The Indian Journal of Agricultural Sciences, 2026)
A study was conducted during 2006-10, seed of six varieties of wheat (Triticum aestivum L.) viz. C 306, PBW 502, WH 542,WH 711, WH 283 and RAJ 3765 were subjected to natural vis-Ã -vis accelerated ageing conditions and evaluated for relative storage potential of the seeds of respective varieties and then accelerated and natural aged seed lot were hydro and osmoprimed to find out the ability of priming treatment in the repair of deterioration sustained during natural and accelerated ageing. Seed quality parameters like germination percent, seedling length, seedling dry weight, vigour indexI and vigour index-II, and electrical conductivity, measured in, natural as well as accelerated aged seed lots. Overall, natural and accelerated ageing reduced germination, seedling length, seedling dry weight, vigour index-I and vigour index-II in all the varieties. However, priming reduced the deleterious effects of ageing and improved all vigour parameters in all the varieties. Hydration with Thiram @ 0.25%. Hydration with GA3(50 ppm for 16-18 hr), hydration with polyethylene glycol (PEG) for 16-18 hr, hydration with KNO3 0.5% (16-18 hr) and hydration with CaCl2 2% for 16-18 hr) were proved beneficial for enhancing all vigour parameters significantly. Among all these priming treatments PEG and GA3 were proved better/superior for increasing all vigour parameters in all the six varieties of wheat.